PENGARUH PEMBERIAN KALIUM TERHADAP FISIOLOGIS DAN MORFOLOGIS KEDELAI PADA CEKAMAN KEKERINGAN - Romi Fahri; Siti Khairani (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Domestic soybean production is weakened by the problem of drought stress that affects all aspects of plant growth and metabolism, while an alternative that can be used is the use of potassium. Potassium is believed to have an important role in increasing plant tolerance to drought. This study aims to examine the effect of potassium application on the physiological and morphological of drought-stressed soybean. The research was conducted in a plastic house in Aras Kabu Village, Beringin Subdistrict, Deli Serdang Regency, North Sumatra using a group randomized design with two factors and three replications. The first factor was soil moisture condition consisting of 80% KL (field capacity) and 40% KL. The second factor was potassium fertilizer application of 100 kg/ha, 200 kg/ha, 300 kg/ha, and no potassium fertilizer. The observed variables were total sugar and leaf area. The results showed that the use of potassium can increase the value of total sugar and leaf area of drought-stressed soybean. Application of K dose of 100 kg/ha (0.5 g/polybag) is the most appropriate to encourage physiological and morphological drought stressed soybean plants.